Knowledge of Songket Cloth Small Medium Enterprise Digital Transformation - Abdillah, Leon A.; Aisyah, Aisyah; Panggabean, Wahdyta Putri; Erkinovich, Sayfiyev Eldor (Politeknik Ganesha Medan, 2024)
This article examines the knowledge of digital transformation of Small and Medium Enterprises (SMEs) that specialize in traditional handicrafts, with a specific emphasis on the Songket textile sector. The study investigates the use of digital technologies, notably blog platforms and the e-commerce site Shopee, to improve and streamline several business processes in Songket textile SMEs. The report takes a case study approach, diving into the experiences of Songket clothing enterprises that have undergone digital transformation. Key areas studied include the use of Blog platforms for brand development, marketing, and consumer involvement, as well as the Shopee E-Commerce platform for online sales and order processing. The essay seeks to give insights into the problems and possibilities faced by Songket cloth SMEs along their digital transformation journey by conducting in-depth observation, interviews, and surveys. The findings add to the scholarly discussion on the digitization of traditional industries, with practical implications for SMEs in the Songket textile sector and other handicraft areas. This study emphasizes the necessity of using digital technologies to preserve and expand traditional crafts, while also throwing light on the potential role of prominent E-Commerce platforms like Shopee in facilitating worldwide market access for such firms.